IMPLEMENTASI AKAD SALAM TERHADAP JUAL BELI SAYURAN DI DUSUN SABUNG REJO DESA BAYU KECAMATAN SONGGON - Annas, Muhamad; Rohman, Fatkhu; Khusnudin, Imam (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
This study aims to determine the implementation of the salam contract on buying and selling in Sumberarum Village, Songgon District. The results of this study indicate that: The implementation of this salam contract is very beneficial for both farmers and collectors because they can find out so far the practice of buying and selling is carried out in accordance with the provisions of the sale and purchase of the salam contract, namely with the concept of not being mutually beneficial on one side and mutually trust between farmers and collectors. The conclusion is the implementation of the salam contract on the sale and purchase of vegetables in Sumberarum Village, Songgon District, identification of applications that occur in the field, measurement through the pillars and conditions and has gone through several long processes so that articles are formed which are obtained and practiced in the field and are in accordance with the provisions of the salam contract.